Impairment of regulatory T cell stability in axial spondyloarthritis: role of EZH2 and pSTAT5 - Mebrek, Majda Lyna; Abaab, Tessnime; Lemeiter, Delphine; Breckler, Magali; Hervé, Roxane; Petit, Mylène; Clavel, Gaëlle; Sigaux, Johanna; Boissier, Marie-Christophe; Semerano, Luca; Biton, Jérôme; Bessis, Natacha (Frontiers in Immunology, 2024)
Background and objectives: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease involving the spine, peripheral joints, and entheses. Functional impairment of regulatory T cells (Treg) is linked to inflammatory diseases, but limited data is available regarding Treg involvement in axSpA. Treg stability refers to their ability to maintain their functions and characteristics in pro-inflammatory environments. EZH2 and phosphorylated STAT5 (pSTAT5) play a critical role in maintaining Treg stability. We aimed to characterize Treg stability in axSpA patients. Methods: Peripheral blood mononuclear cells (PBMCs) from axSpA patients, either naïve from targeted therapy or treated by TNF inhibitors (TNFi), and from healthy donors (HD), were freshly isolated. Expression of stability (EZH2, pSTAT5) and suppressive (TNFR2 and CD39) markers by Treg was analyzed by flow cytometry. Results: EZH2 expression by Treg was decreased in axSpA patients as compared to HD (p<0.01). Mechanistic study showed that inhibition of EZH2 attenuated Treg differentiation and suppressive phenotype in vitro. EZH2 was predominantly expressed by highly suppressive TNFR2 + and CD39 + Treg. Additionally, axSpA patients exhibited a reduced frequency of pSTAT5 + Treg compared to HD (p<0.05), and pSTAT5 + Treg frequency increased at 3 months of TNFi treatment compared to baseline (p<0.05). This last result suggested a restoration of Treg stability upon TNFi treatment. Conclusion: By highlighting a deficient expression of EZH2 and pSTAT5 by Treg, we revealed an impaired Treg stability in axSpA. Deciphering the pathways influenced by these molecules is necessary to assess the potential therapeutic benefits of restoring Treg stability in axSpA.